2003
DOI: 10.1002/humu.10216
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis in patients with N-acetylglutamate synthase deficiency

Abstract: N-acetylglutamate synthase (NAGS) is the key enzyme for the regulation of the hepatic urea cycle and is also highly expressed in kidney and gut. The reaction product, N-acetylglutamate, is an allosteric activator of carbamylphosphate synthetase 1 in the liver, catalyzing the initial step of ammonia detoxification. NAGS deficiency is a rare inborn error of metabolism inherited as an autosomal recessive trait leading to hyperammonemia. Using homology search based on genetic information of ascomycetes, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…NAGS deficiency is an autosomal recessive disorder that appeared to be the least prevalent of all urea cycle disorders [Brusilow and Horwich, 2001]. However, the apparent low prevalence may have been biased because the liver-enzyme assay requires an open biopsy, is technically difficult, and is not completely reliable [Colombo et al, 1982;Heckmann et al, 2005], and molecular diagnosis of NAGS deficiency has only recently been possible [Caldovic et al, 2003;Elpeleg et al, 2002;Haberle et al, 2003b]. NAGS was the last urea cycle gene to be cloned [Caldovic et al, 2002b].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…NAGS deficiency is an autosomal recessive disorder that appeared to be the least prevalent of all urea cycle disorders [Brusilow and Horwich, 2001]. However, the apparent low prevalence may have been biased because the liver-enzyme assay requires an open biopsy, is technically difficult, and is not completely reliable [Colombo et al, 1982;Heckmann et al, 2005], and molecular diagnosis of NAGS deficiency has only recently been possible [Caldovic et al, 2003;Elpeleg et al, 2002;Haberle et al, 2003b]. NAGS was the last urea cycle gene to be cloned [Caldovic et al, 2002b].…”
mentioning
confidence: 99%
“…The gene is located on the long arm of chromosome 17 within band 17q21.31 [Caldovic et al, 2002a]. The gene spans 4.5 kb, has an open reading frame of 1,605 nucleotides, and contains seven exons and six introns [Caldovic et al, 2002a[Caldovic et al, , 2002bHaberle et al, 2003b]. NAGS is expressed in the liver and intestine and possibly to a lesser degree in other tissues [Caldovic et al, 2002b].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the current alignment, 197 amino acids are identical across vertebral species. Deleterious mutations of NAGS have been identified in patients corresponding to these regions of strong conservation [13,31,33].…”
Section: Other Mutationsmentioning
confidence: 99%
“…Moreover, a specific treatment for NAGS deficiency using Ncarbamylglutamate, a NAG structural analog, to activate CPSI is available and approved for use in Europe (Carbaglu®, Orphan Europe). Several reports have shown that carbamylglutamate is apparently effective in the treatment of NAGS deficiency [31,[33][34][35][36][37][38]. With the availability of molecular diagnosis, early confirmation of NAGS deficiency becomes particularly compelling, as treatment with N-carbamylglutamate may be effective in preventing hyperammonemia and brain damage.…”
Section: Treatmentmentioning
confidence: 99%